Impure Thoughts : Sexuality, Catholicism and Literature in Twentieth-Century Ireland. - Cronin, Michael G. (Manchester University Press, 2017)
This book will be of interest to students and scholars in various disciplines, including literary studies, history, sociology and gender studies.